3D wind buckling analysis of long steel corrugated silos with vertical stiffeners. (August 2018) - Maleki, Shervin; Mehretehran, Alireza Moazezi
Abstract: Thin-walled cylindrical steel silos are susceptible to instability under wind pressure when they are empty or only partially filled. This paper investigates numerically the wind buckling behavior of a real steel corrugated silo with 8.02 m diameter and 17.62 m height, strengthened by open-section vertical stiffeners. Accordingly, comprehensive 3D finite element models were used and detailed linear and non-linear buckling analyses were conducted. The effects of sinusoidal corrugated sheet profile dimensions on this issue were specially explored. Wind load vertical and circumferential distributions were adopted from Eurocode. Two proposed circumferential pressure distributions for an isolated silo and a silo in a group were taken into consideration. To investigate the material efficiency of corrugated steel silos, a comparison between a full-scale corrugated silo and an equivalent flat sheets one was performed. Additionally, imperfection sensitivity analyses for both structures were carried out. Graphical abstract: Highlights: A comprehensive wind buckling assessment of a real corrugated silo is conducted. 3D linear and non-linear analyses of perfect and imperfect silos are performed. Wind distribution for an isolated silo and a silo in a group are considered. Comparative buckling analyses of corrugated and flat sheets silos are carried out.